Hunting Gravitational Waves with Multi-Messenger Counterparts: Australia's Role. (17th December 2015) - Howell, E. J.; Rowlinson, A.; Coward, D. M.; Lasky, P. D.; Kaplan, D. L.; Thrane, E.; Rowell, G.; Galloway, D. K.; Yuan, Fang; Dodson, R.; Murphy, T.; Hill, G. C.; et al.
Abstract: The first observations by a worldwide network of advanced interferometric gravitational wave detectors offer a unique opportunity for the astronomical community. At design sensitivity, these facilities will be able to detect coalescing binary neutron stars to distances approaching 400 Mpc, and neutron star–black hole systems to 1 Gpc. Both of these sources are associated with gamma-ray bursts which are known to emit across the entire electromagnetic spectrum. Gravitational wave detections provide the opportunity for 'multi-messenger' observations, combining gravitational wave with electromagnetic, cosmic ray, or neutrino observations. This review provides an overview of how Australian astronomical facilities and collaborations with the gravitational wave community can contribute to this new era of discovery, via contemporaneous follow-up observations from the radio to the optical and high energy. We discuss some of the frontier discoveries that will be made possible when this new window to the Universe is opened.